2021
DOI: 10.1186/s12890-021-01482-x
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing physical activity in adults with cystic fibrosis

Abstract: Background Physical activity (PA) is a well-documented and accepted adjunct therapy for the maintenance and improvement of long-term health in cystic fibrosis (CF). Although the benefits of PA for CF populations are well-established, adherence to PA programmes within this population remains low. This study aimed to investigate the factors that influence engagement in physical activity, and to explore exercise preferences, among adults with cystic fibrosis (CF). Me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 32 publications
2
19
0
Order By: Relevance
“…Translating this evidence into clinical practice has had limited success, though it has previously been proposed that increasing levels of habitual PA may be more feasible and result in greater compliance than conventional exercise training inventions [ 5 ]. Despite this, there are few examples of research exploring perceptions of PA among adults with CF and despite many of the barriers and facilitators identified being similar to those already identified in children such as fluctuating health and competing interests, some were specific to adult populations and typically associated with advanced disease severity which may warrant further investigation [ 11 , 12 ]. As with a recent systematic review of qualitative studies exploring correlates of PA among children with CF, the current research seeks to utilise a sociological model to understand the multiple layers of influence on PA behaviour, which is yet to done in adults with CF [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Translating this evidence into clinical practice has had limited success, though it has previously been proposed that increasing levels of habitual PA may be more feasible and result in greater compliance than conventional exercise training inventions [ 5 ]. Despite this, there are few examples of research exploring perceptions of PA among adults with CF and despite many of the barriers and facilitators identified being similar to those already identified in children such as fluctuating health and competing interests, some were specific to adult populations and typically associated with advanced disease severity which may warrant further investigation [ 11 , 12 ]. As with a recent systematic review of qualitative studies exploring correlates of PA among children with CF, the current research seeks to utilise a sociological model to understand the multiple layers of influence on PA behaviour, which is yet to done in adults with CF [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The CFQ-R respiratory domain outcomes in our review highlights that pwCF may perceive exercise as beneficial for their respiratory system function, despite the lack of improvement in objective ppFEV 1 performance; thus highlighting the importance of including both objective, physical function, and subjective, psychological function, when evaluating interventions in disease groups. Interestingly, for the CFQ-R respiratory domain, reduced adherence was reported in both of the included studies that showed reduced scores [ 31 , 33 ], and within the wider CF population, it has been reported that adherence to conventional exercise programmes has been suboptimal [ 9 , 40 , 41 ]. For example, Rovedder et al [ 30 ] indicated that higher QoL scores were related to participants who performed more frequent telemedicine-based exercise, and highlighted the importance of adherence to tailored long-term programmes that meets the specific needs and preferences of pwCF.…”
Section: Discussionmentioning
confidence: 99%
“…The commonly used outcome measures to assess lung function and QoL in pwCF are percentage predicted forced expiratory volume in one second (ppFEV 1 ) and the Cystic Fibrosis Questionnaire–Revised (CFQ-R) [ 7 , 8 ]. Cystic fibrosis cannot be cured, therefore maintaining lung function and improving QoL of pwCF is a key focus [ 7 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are number of potential reasons for the high percent body fat found in many of our patients at the time of admission. In addition to acute illness, these include a small skeletal muscle mass, owing to a previous sedentary lifestyle, 31 and preference for or family reliance on high glycemic, low protein foods 32,33 . Yet another factor is CFTR modulator therapy 6,7,34–36 .…”
Section: Discussionmentioning
confidence: 99%